Ekstraksi Fitur MFCC pada Lagu Gundhul Pacul - Roger Julian Sitorus; I Gede Santi Astawa (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
MFCC is an effective method in audio feature extraction, including in song and music analysis. This method involves converting the frequency spectrum of the audio signal into the Mel scale, which is more in line with human auditory perception, and then calculating the cepstral coefficient. The results of the MFCC feature extraction on the song